Brain activity at 70-80 Hz changes during olfactory stimulation protocols in Drosophila. - Lucia L Prieto-Godino (Public Library of Science (PLoS), 2010)
Oscillatory and synchronized activities in the mammalian brain have been correlated with the execution of complex cognitive tasks. Similar oscillations have been observed in local field potentials (LFPs) in flies, in this case correlated with different attentional states. To further test the significance of these oscillations we recorded LFPs from the brain of Drosophila melanogaster as it responded to the presentation of olfactory stimuli. We find that responses in the 70-80 Hz range increase during olfactory stimulation. Recurrent stimulation specifically decreased the power of LFPs in this frequency range. Delivery of electric shocks before olfactory stimulation modulated LFPs in the 70-80 Hz range by evoking a transient increase. These results suggest that these signals are a simple neuronal correlate of higher-order olfactory processing in flies.